Biofortification of Cilantro (Corriandrum sativum) in Relation to Calcium, Iodine and Selenium Application - Abbas, Tahira; Altaf, Khadija; Ahmad, Waqas; Butt, Madiha; Wahocho, Niaz Ahmed; Jamali, Muzamil Farooq (Journal of Agriculture and Biology, 2025)
Micronutrients and macronutrients are the key elements of a healthy diet. The micronutrient iodine and selenium are essential trace elements which are mostly obtained by food or supplements and Calcium is the 5th most abundant macro element important for proper functioning of body. The purpose of this research focused to identify the appropriate the dose and application way of these mineral elements for improving the nutrient status of vegetables for improving the human diet. Certified seeds of cilantro were obtained from an authorized nursery and sown in trays at the depth of 2 inches. The study consisted of four treatment conditions; iodine, selenium, calcium and control treatment. Three replications of each treatment were planned, comprised of one tray. The harvested produce was evaluated for different morphological (plant fresh and dry weight, shoot and root length, number of leave and leaf diameter), biochemical parameters (Total soluble solids, Vitamin c, acidity, carotenoids, chlorophyll contents, lipophilic antioxidant(LPA), starch contents, amino acids, carotenoids, flavonoids, phenolic contents) and ionic contents (I, Se and calcium). The results demonstrated that supplementation with iodine @2.5mg/L, selenium @1mg/L and Calcium @200ppm were optimal doses for maintaining the plant health and increased the accumulation in edible parts of cilantro plants. Iodine application @2.5mg reached maximum 205.76µg in foliar parts and 254.43µg in roots while selenium @1mg concentrations reached 230µg and 220mg in foliar and basal plant parts. However, highest calcium contents were quantified in Ca @200ppm concentration. These levels are sufficient to meet the world health organization’s daily recommended doses of I, Se and Ca.
Keywords: Micronutrients; Macronutrients; Iodine; Selenium; Calcium; Cilantro; Nutrient Biofortification; Plant Morphology; Biochemical Parameters; Ionic Contents